Effect and Impact of the Coronavirus Pandemic (COVID-19) on Tourism Industry in India: A review. (2020) - Jamal, Abdul; Sankaran, Arumugam; Hameed, Shahul; Sultana, Siham El-Kafafi and Yasmeen
No abstract available